(3ebGeGJ GdSjhWis - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3ef ebGeI SGLYI GdMQe bhdg(B:- ((3Ef Chd HjJ hVY ddfGS ddPi HHcI eHGQckG hgOi ddYGdejf ajg BjGJ HjfGJ ebGe EHQGgje , hef ONdg cGf BefG(B) s
(3BNQgG (B:s
(3ef ebGeI beY GdeYGQV ai fUQI GHf GdaGQV bhdg(B: (3EdG hbO aQVJ Ydjg RjGOI GHf GdaGQVef JMJ GdYGQV s
(3HgG fXGe GdJYbjHIs
(3HChdgG agQS ddebGeGJs
(3fSNI KGfjI YOJgG CQHY hYTQhf ebGeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B86 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1785s
Keywords: (3GdCOHs